Circular RNAs in the human brain are tailored to neuron identity and neuropsychiatric disease - Xianjun Dong; Yunfei Bai; Zhixiang Liao; David Gritsch; Xiaoli Liu; Tao Wang; Rebeca Borges-Monroy; Alyssa Ehrlich; Geidy E. Serrano; Mel B. Feany; Thomas G. Beach; Clemens R. Scherzer (Nature Communications, 2023)
Abstract Little is known about circular RNAs (circRNAs) in specific brain cells and human neuropsychiatric disease. Here, we systematically identify over 11,039 circRNAs expressed in vulnerable dopamine and pyramidal neurons laser-captured from 190 human brains and non-neuronal cells using ultra-deep, total RNA sequencing. 1526 and 3308 circRNAs are custom-tailored to the cell identity of dopamine and pyramidal neurons and enriched in synapse pathways. 29% of Parkinson’s and 12% of Alzheimer’s disease-associated genes produced validated circRNAs. circDNAJC6, which is transcribed from a juvenile-onset Parkinson’s gene, is already dysregulated during prodromal, onset stages of common Parkinson’s disease neuropathology. Globally, addiction-associated genes preferentially produce circRNAs in dopamine neurons, autism-associated genes in pyramidal neurons, and cancers in non-neuronal cells. This study shows that circular RNAs in the human brain are tailored to neuron identity and implicate circRNA-regulated synaptic specialization in neuropsychiatric diseases.